2007
DOI: 10.1177/0363546506293898
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Collagen Fibril Alterations in the Patellar Tendon 6 Years after Harvesting Its Central Third

Abstract: Six years after harvesting its central third and leaving the defect open, the patellar tendon revealed a "more heterogeneous matrix" with changes in ultrastructural morphology and relative fibril diameter distribution compared with normal control tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
3
25
0
2
Order By: Relevance
“…Furthermore, in the present study, ϳ25% of the fibrils in the specimen from the patellar tendon had a small diameter (between 0 and 60 nm). This is in contrast to young subjects (27 yr, range 19 -40 yr), in whom ϳ73% of the fibrils had a diameter Ͻ60 nm (54). Taken together, these findings suggest an altered balance between collagen synthesis and breakdown with aging in women.…”
Section: Tendon Csa and Fibril Characteristicsmentioning
confidence: 63%
See 1 more Smart Citation
“…Furthermore, in the present study, ϳ25% of the fibrils in the specimen from the patellar tendon had a small diameter (between 0 and 60 nm). This is in contrast to young subjects (27 yr, range 19 -40 yr), in whom ϳ73% of the fibrils had a diameter Ͻ60 nm (54). Taken together, these findings suggest an altered balance between collagen synthesis and breakdown with aging in women.…”
Section: Tendon Csa and Fibril Characteristicsmentioning
confidence: 63%
“…For test of differences in the distribution of fibrils between groups, the fibrils were divided into three intervals: Ͻ60 nm, 60 -90 nm, and Ͼ90 nm. The intervals chosen were based on earlier published results (54). The individual values for the biomechanical test parameters were analyzed at the same individual common force and the same common force for all of the subjects (29).…”
Section: Statistics and Data Analysesmentioning
confidence: 99%
“…28,34,35 Previous histochemical and ultrastructural study of the patellar tendon donor site showed that it does not normalize over time. 6,25,35 We showed that the patellar tendon had a significantly smaller gap size in the PRP group than in the control cases To verify the possibility of thickening or shortening of the patellar tendon, we also evaluated tendon thickness and length and showed no difference between the groups. As secondary objectives, we evaluated the clinical and functional outcomes of ACL reconstruction comparing both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Os ensaios clínicos empregando o PRP em tendões e ligamentos, como roturas do tendão calcâneo (15) , tendinopatia patelar (16,17) e do calcâneo (18) , epicondilite do cotovelo (14) , e lesões do ligamento cruzado anterior (LCA) (20,21) (35)(36)(37) , com estudos por ressonância magnética seriada (38)(39)(40)(41) e até mesmo histológicos (42,43) . Observa-se uma redução progressiva do defeito, que persiste por vários anos (40,41) .…”
Section: Introductionunclassified
“…Observa-se uma redução progressiva do defeito, que persiste por vários anos (40,41) . O tecido regenerado apresenta matriz extracelular heterogênea, fibras colágenas desorganizadas, hipercelularidade, e propriedades mecânicas inferiores (43,44) .…”
Section: Introductionunclassified